Dixie Cox Marie dressed in fancy Western wear costume on stage - Sahl, Ted (photographer):::Creator::::::::::::
Dixie Cox Marie in fancy Western dress costume wearing black hat, boots, spurs and gun holster while smoking a cigar. Appears to be on the stage of the Savoy nightclub in Cupertino. Other men in Western wear cheer in the background.